Effect of strawberry (Fragaria × ananassa) leaf extract on diabetic nephropathy in rats - Ibrahim, Doaa S (Int J Exp Pathol, 2015)
Diabetic nephropathy is a clinical syndrome characterized by albuminuria, hypertension and progressive renal insufficiency. The aim of this study was to investigate the effect of strawberry (Fragaria × ananassa) leaf extract on diabetic nephropathy in rats. Streptozotocin (STZ) diabetic rats were orally treated with three doses (50, 100 and 200 mg/kg) of strawberry leaf extract for 30 days. Nephropathy biomarkers in plasma and kidney were examined at the end of the experiment. The three doses of strawberry leaf extract significantly decreased the levels of blood glucose, urea nitrogen, plasma creatinine, kidney injury molecule (Kim)-1, renal malondialdehyde (MDA), tumour necrosis factor alpha (TNF-α), interleukin (IL)- 6 and caspase-3 in diabetic rats. Meanwhile, the levels of plasma insulin, albumin, uric acid, renal catalase (CAT), superoxide dismutase (SOD) and vascular endothelial growth factor A (VEGF-A) were significantly elevated in diabetic rats treated with strawberry leaf extract. These results indicate the role of strawberry leaves extract as anti-diabetic, antioxidant, anti-inflammatory and anti-apoptosis in diabetic nephropathy.